Selection of new branch location with SWARA, ARAS and WASPAS methods: An example of a cargo company in the logistics sector - Nebati, Emine Elif; Vatansever, Eda Nur; Makas, Gülnihal (Fırat University, 2023)
The establishment location is the place where businesses maintain their main activities and economic lives. As the decision of the establishment location is costly and takes a long time to compensate, it is paramount for businesses to make the right choice for location. In cargo businesses, the choice of establishment location is one of the important activities that affect the competitive advantage and operational efficiency in the market. Many quantitative methods are utilized when deciding on the establishment location which is called the "living space" of the business. In the study, determining the criterion importance weights in location selection with the SWARA (Step-Wise Weight Assessment Ratio Analysis) method, which is one of the MCDM (Multi-Criteria Decision Making) techniques, WASPAS (Weighted Aggregated Sum Product Assessment) and ARAS (Additive Ratio Assessment) methods were used comparatively to determine the most optimal value and appropriate location for the businesses. Within the scope the model, a total of 20 criteria, including 5 main and 15 sub-criteria, and 3 location alternatives were determined. Due to the scarcity of the studies in the literature on the topic and the proposed approach, it is aimed to assist other studies with the subject and implementation of the study. Based on findings, it has been revealed that the most important criterion is “location” and the most suitable alternative for the new branch of the business is “Esenyurt” according to the both methods.

Kuruluş yeri işletmelerin temel faaliyetlerini, ekonomik hayatlarını sürdürdükleri yerdir. Kuruluş yeri seçimi, maliyetli ve telafisi uzun zaman aldığından doğru seçim yapmak işletmeler için büyük önem arz etmektedir. Kargo işletmelerinde de kuruluş yeri seçimi kararı piyasadaki rekabet üstünlüğü ve işletme verimliliğini etkileyen önemli faaliyetlerden biridir. İşletmelerin “yaşam alanı” olarak adlandırılan kuruluş yeri seçimine karar verilirken çeşitli sayısal yöntemlerden yararlanılmaktadır. Bu çalışma ile ÇKKV (Çok Kriterli Karar Verme) tekniklerinden SWARA (Step-Wise Weight Assessment Ratio Analysis) yöntemiyle şube yeri seçiminde kriter önem ağırlıklarının belirlenmesi WASPAS (Weighted Aggregated Sum Product Assessment) ve ARAS (Additive Ratio Assessment) yöntemleri karşılaştırmalı kullanılarak işletme için en uygun yerin belirlenmesi amaçlanmıştır. Önerilen model kapsamında, 5 ana kriter ve 15 alt kriter olmak üzere toplam 20 kriter belirlenmiş ve 3 yer alternatifi sunulmuştur. Seçilen konu ve önerilen yaklaşım ile ilgili literatürde sınırlı sayıda çalışma bulunmasından dolayı, bu çalışmanın konusu ve uygulamasıyla diğer çalışmalara yardımcı olması amaçlanmıştır. Çalışma bulgularına göre, en önemli kriterin “Konum” ve işletmenin yeni şubesi için en uygun alternatifin her iki yöntemde de “Esenyurt” olduğu belirlenmiştir.
SWARA, ARAS ve WASPAS Yöntemleri ile Yeni Şube Yeri Seçimi: Bir Kargo Firması Örneği